(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND The imaging method most frequently employed to identify brain areas involved in neuronal processing of nociception and brain pain perception is blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI). Arterial spin labelling (ASL), in contrast, offers advantages when slow varying changes in brain function are investigated. Chronic pelvic pain syndrome (CPPS) is a disorder of, mostly, young males that leads to altered pain perceptions in structures related to the pelvis. We aimed to investigate the potential of ASL to monitor longitudinal cranial blood flow (CBF) changes in patients with CPPS. METHODS In a randomised, placebo-controlled, double-blind single centre trial, we investigated treatment effects in CPPS after 12 weeks in patients that underwent sono-electro-magnetic therapy vs placebo. We investigated changes of CBF related to treatment outcome using pseudo-continuous arterial spin labelling (pCASL)-MRI. RESULTS We observed CBF downregulation in the prefrontal cortex and anterior cingulate cortex and upregulation in the dorsolateral prefrontal cortex in responders. Nonresponders presented with CBF upregulation in the hippocampus. In patients with a history of CPPS of less than 12 months, there were significant correlations between longitudinal CBF changes and the Chronic Prostatitis Symptom Index pain subscore within the joint clusters anterior cingulate cortex and left anterior prefrontal cortex in responders, and the right hippocampus in nonresponders. CONCLUSIONS We demonstrated therapy-related and stimulus-free longitudinal CBF changes in core areas of the pain matrix using ASL. ASL may act as a complementary noninvasive method to functional MRI and single-photon emission computed tomography / positron emission tomography, especially in the longitudinal assessment of pain response in clinical trials. (Trial registration number NCT00688506)